Grid and Cluster Computing - Prabhu C.S.R (Prentice Hall of India, 2008)
Grid computing and cluster computing are advanced topics and latest trends in computer science that find a place in the computer science and information technology curricula of many engineering institutes and universities today. Divided into two parts- part i, grid computing. Part ii, cluster computing-, this compact and concise text strives to make the concepts of grid computing and cluster computing comprehensible to the students through its fine presentation and accessible style. Part i of the book enables the student not only to understand the concepts involved in grid computing but also to build their own grids for specific applications.similarly, as today supercomputers are being built using cluster computing architectures, part ii provides an insight into the basic principles involved in cluster computing and equips the readers with the knowledge to build their own clusters in-house. Diagrams are used to illustrate the concepts discussed and to enable the reader to actually construct a grid or a cluster himself. The book is intended as a text for undergraduate and postgraduate students of computer science and engineering, information technology (b.tech./m.tech. Computer science and engineering/it), and post-graduate students of computer science/information technology (m.sc. Computer science and m.sc. It). Besides, practising engineers and computer science professionals should find the text very useful.